A Construction of Bent Functions of n+2 Variables from a Bent Function of n Variables and Its Cyclic Shifts. (17th April 2014) - Climent, Joan-Josep; García, Francisco J.; Requena, Verónica
Abstract : We present a method to iteratively construct new bent functions of n + 2 variables from a bent function of n variables and its cyclic shift permutations using minterms of n variables and minterms of 2 variables. In addition, we provide the number of bent functions of n + 2 variables that we can obtain by applying the method here presented, and finally we compare this method with a previous one introduced by us in 2008 and with the Rothaus and Maiorana-McFarland constructions.